Algorithmic prediction of commercial contracts concluded within the framework of commercial companies: Economic, legal, jurisprudential study - GRAZZA, Belkis; KASSAA, Souad (Journal of Human Sciences, 2025)
This research paper aims to theorize the proposed technical approach based on AI algorithms it is called APRECON "the technique of algorithmic prediction in commercial contracts", and the generality of adopting the technique was allocated in the study to commercial companies, thus the gist of this technique is the prediction of international commercial contracts and the subsequent proposals suitable for commercial companies qualified to contract with them within the framework of each type of the predicted contract. The study conducted that this technique is appropriate to adopt due to the economic effects it achieves, and the possibility of being subject to restrictions in the light of current absence of legislation that would regulate the work of smart predictive algorithm, in addition to the legitimacy of adopting it according to the Islamic jurisprudence and the necessity of taking in account a set of jurisprudential controls.